Survey on community detection method based on random walk - Yang GAO; Hongli ZHANG (Tongxin xuebao)
Random walk techniques achieve high accuracy and efficiency in community detection.To summarize and analyze community detection methods based on random walk, the random walk technique was classified into personalized PageRank, heat kernel diffusion and other random walk methods, and community detection was classified into tasks of local community detection and global community structure identification.A detailed overview of different techniques based on random walk and their application to the tasks of community detection was provided, problems in existing methods were analyzed, and future research directions were pointed out.Finally, evaluation metrics of community detection accuracy for different community detection tasks were summarized in terms of similarity and structure respectively to facilitate research in community detection.